Analisa Kontribusi Pajak Kendaraan Bermotor Terhadap Pendapatan Asli Daerah Pada BPRD DKI Jakarta - Seno Sudarmono Hadi (Universitas Bina Sarana Informatika, 2018)
Badan Pajak dan Retribusi Daerah DKI Jakarta is an organization that performs its duties as a regional revenue manager in the collection of taxes and user charges in DKI Jakarta. Motor Vehicle Tax is a Regional Tax that contributes considerably in order to increase local original income. The purpose in this study is the analysis of the contribution of motor vehicle tax to the original revenue area at the DKI Jakarta Regional Tax and Retribution Agency. Data collection methods used are documentation studies, observation and interviews. The method of data analysis is a qualitative analysis, ie an analysis that is not based on statistical calculations that are quantitative (sum) and presented systematically. The result of the research shows that the percentage fluctuation of PKB contribution to PAD from year to year. PKB contribution to PAD in fiscal year 2012 amounted to 18.63% decreased in fiscal year 2013 by 1.48 points (17.15%). Then in fiscal year 2014 the contribution of PKB to PAD decreased again by 1.23 points (15.92%). However, in two years PKB's contribution to PAD has increased, in fiscal year 2015 the contribution of PKB to PAD has increased by 2.13 points (18.05%) and budget year 2016 PKB contribution to PAD has increased by 0.81 points (18, 86%). . Keywords: Motor Vehicle Tax, Local Tax, Local Original Income, Vehicle Tax Contributions